Biomolecular assemblies through weak noncovalent interactions: Higher-order transient structures and their condensate phase - Roderick MacKinnon; Christoph A. Haselwandter (Proceedings of the National Academy of Sciences, 2026)
Recent data suggest that many membrane proteins spontaneously organize into spatial patterns through weak noncovalent interactions. These weak interactions are protein type-specific and underlie the formation of higher-order transient structures (HOTS), which can function as 10 to 100 nanometer-sized, transient hubs of membrane signaling. We describe the necessary conditions for HOTS assembly to occur, its thermodynamic relationship to biomolecular condensate formation, and potential roles of HOTS in biology stemming from their unique physical properties. Currently, a quantitative understanding of HOTS is limited to membrane proteins, but many observations suggest that HOTS may also be abundant in three-dimensional cellular compartments.